Human resource audit in the academic libraries in Butuan City using the Philippine Association of Academic and Research Libraries (PAARL) standard - Estrella, Faith Anemone O. (1997)
This thesis on Human Resource Audit on the Academic libraries in Butuan City is developed to look into the status of libraries in eight colleges. The study sought to know their qualifications and the training they have acquired to make them efficient librarians; to bring to the administration's awareness the problems and deficiencies faced by each of the libraries studied with regard to the human resources factors; to urge the administration to involve their librarians to participate in curriculum planning and other decision making that involves the library's role in the academic structure; and to urge these libraries to apply the proposed PAARL standard in their respective libraries.